The Effect of Product Innovation, Brand Image and Word of Mouth on Interest in Buying Maybelline Face Powder in Gen-Z Students Of Feb Nasional University - Radina Salsabila; Subur Karyatun; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the influence of Product Innovation, Brand Image and Word of Mouth on Interest in Buying Maybelline face powder products in Gen-z FEB National University Students. The research method used is a quantitative method and uses multiple linear regression analysis with processing using Statistical Product and Service Solutions (SPSS) version 25 with data collection methods through questionnaires to 100 respondents from FEB Nasional University students and know Maybelline face powder products. The results of this study indicate that the Product Innovation variable has a positive and significant effect on Buying Interest for Maybelline face powder products on Gen-z, Brand Image has a positive and significant effect on Buying Interest for Maybelline face powder products on Gen-z, Word of Mouth has a positive and significant effect on Interest Buy Maybelline face powder products on Gen-z